Development of a New Cold Metal Transfer Arc Additive Die Manufacturing Process - An Zhang; Yanfeng Xing; Fuyong Yang; Xiaobing Zhang; Hongze Wang; Tiejun Yu (Advances in Materials Science and Engineering)
Due to its high efficiency, cold metal transfer (CMT) arc additive manufacturing presents considerable potential in the aluminium alloy additive manufacturing industry. However, during CMT arc additive manufacturing, the surrounding air environment promotes the lateral flow of liquid aluminium and the instability of the molten pool, reduces the surface quality and material utilisation of deposition walls, and causes internal hydrogen pores and coarse columnar grains, which negatively affect the structure and mechanical properties of the deposition walls. This study developed a CMT arc additive die manufacturing process to control the substrate material and deposition path to improve the physical properties of the deposition wall. The experimental results indicated that the copper plates can affect molten pool flow and material formation in the additive process, minimise hydrogen pores, and refine columnar grains. The porosity dropped from 2.03% to 0.93%, and the average grain size decreased from 16.2 ± 1.4 to 13.6 ± 1.3 μm, thereby enhancing the structure and mechanical properties of the deposition wall to attain standard additive manufacturing products.